Imaging Characteristics of Mismatch Lesions: An Angiographic and Intravascular Ultrasound Analysis of 1369 Coronary Lesions. (September 2019) - Phan, Tan Quang; Nguyen, Lan Hieu; Nguyen, Lan Viet; Lee, Wang Soo; Won, Hoyoun; Cho, Iksung; Shin, Seung Yong; Sharmin, Saima; Thottian, Julian Johny; Kim, Sang-Wook
Objectives: To evaluate the angiographic and intravascular ultrasound (IVUS) characteristics of coronary mismatch lesions. Background: Better understanding about the characteristics of mismatch lesions may help to achieve more accurate lesion assessment and, thereby, to improve the outcomes of percutaneous coronary intervention (PCI). Methods: Angiographic and IVUS data from 1369 lesions were analyzed. Mismatch lesion was defined as the difference between proximal and distal reference lumen diameters of ≥1.0 mm or ≥30% of the distal reference lumen diameter. Results: The incidence of mismatch lesions was 20.1% (275/1369). Compared to nonmismatch group, mismatch group had longer lesions (21.3 [6.4] mm vs 18.4 [6.4] mm, P < .001) with smaller minimum lumen diameter (0.87 [0.29] mm vs 1.10 [0.31] mm, P < .001) and more severe diameter stenosis (78.8% [9.2%] vs 66.3% [10.3%], P < .001). On IVUS, mismatch group had larger lumen area (18.7 [5.0] vs 15.8 [5.1] mm 2, P < .001) but lower plaque burden at the proximal reference segment (41.0% [9.2%] vs 45.7% [9.9%], P < .001) and smaller lumen area (4.83 [1.89] vs 7.36 [2.89] mm, P < .001) but higher plaque burden at the distal reference segment (42.9% [10.4%] vs 41.4% [10.1%], P = .023). Multivariable logistic regression analysis showed that mismatch lesions were frequently accompanied by diffuse lesions (odds ratio [OR] = 2.50; 95% confidence interval [CI]: 1.83-3.40; P < .001), bifurcation lesions (OR = 5.83; 95% CI: 4.40-7.74; P < .001), and lesions with a low TIMI flow grade (OR = 1.70; 95% CI: 1.08-2.67; P = .022) or severe diameter stenosis (OR = 3.05; 95% CI: 2.10-4.43; P < .001). Conclusions: Mismatch lesions are quite common and characterized by greater lesion complexity compared with nonmismatch lesions. Further studies may be necessary to address the impact of this lesion type on the outcome of PCI.